2021
DOI: 10.1021/acs.energyfuels.0c03028
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Basic and Non-basic Nitrogen Compounds during Heavy Oil Hydrotreating on Two Typical Catalyst Gradations

Abstract: Hydrodenitrogenation (HDN) is still a challenging process that many refineries need to overcome. The influence of catalysts on HDN efficiency cannot be ignored. In this study, Qilu atmospheric residue was subjected to a pilot-scale continuous hydrotreater, and liquid products were obtained from four outlets under two typical catalyst gradations. Basic nitrogen (BN) and non-basic nitrogen (NBN) compounds in the feedstock and liquid products were investigated by positive and negative (±) electrospray ionization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Many studies concerned the transformation of nitrogen compounds in the refining process, especially hydrotreating. , Fu et al first used ESI FT-ICR MS for this purpose and presented an excellent work on the characterization of nitrogen-concentrated vacuum gas oils before and after hydrotreating. The results indicated that compounds having multiple heteroatoms are more susceptible to hydrotreatment than those having only one heteroatom.…”
Section: Applications For Polar Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies concerned the transformation of nitrogen compounds in the refining process, especially hydrotreating. , Fu et al first used ESI FT-ICR MS for this purpose and presented an excellent work on the characterization of nitrogen-concentrated vacuum gas oils before and after hydrotreating. The results indicated that compounds having multiple heteroatoms are more susceptible to hydrotreatment than those having only one heteroatom.…”
Section: Applications For Polar Compoundsmentioning
confidence: 99%
“…Lai et al reported successful isolation of basic nitrogen compounds from the vacuum gas oil and its hydrotreated product by the formation of complexes coordinated with FeCl 3 . ESI FT-ICR MS revealed the transformation of basic nitrogen compounds in hydrotreating. ,,,,,,, The basic nitrogen compounds from the vacuum gas oil with short alkyl chains can be preferentially removed by hydrotreatment. Partially saturated products of the basic nitrogen compounds were widely found in the hydrotreated vacuum gas oil .…”
Section: Applications For Polar Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Petroleum crude oil and its derived samples contain undesirable nitrogen-containing compounds (NCCs), which are conventionally classified into basic nitrogen species (pyridine, quinoline, and alkylated benzoquinolines) and non-basic nitrogen species (pyrrole, indole, carbazole, and benzoalkylated analogues). , In general, NCCs in petroleum are N-heterocyclic aromatic structures. The non-basic species have a lone pair of electrons as a constituent of the π-aromatic system, promoting more stability and hindering their removal by conventional reactions in the petroleum industry. , Nowadays, the maximum content of NCCs in petroleum is limited to less than 1 ppm and is also monitored with regard to storage stability, thermal stability, and gum content (5 mg/100 mL in most fuels)…”
Section: Introductionmentioning
confidence: 99%
“…The non-basic NCCs play an essential role in geochemical studies and are considered migration and molecular maturation markers. , Moreover, these compounds in petroleum lead to catalyst poisoning in cracking processes and compromise the stability of petroleum-derived samples, reducing the fuel economy. , Among non-basic NCCs, pyrroles are one of the most interfering compounds in fuel stability. , The formation of polymers by autoxidation by the free radical reaction is commonly observed because the carbon adjacent to the nitrogen atom in the pyrrole ring is easily oxidized. , Autoxidation also leads to hydroperoxides and other oxygenated compounds. , Therefore, the amount of non-basic species is directly correlated with the quality of petroleum-derived samples.…”
Section: Introductionmentioning
confidence: 99%